Penerapan Progressive Musscle Relaxation Terhadap Penurunan Kualitas Hidup Dan Ansietas Pada Pasien Skizofrenia Paranoid - Rahayu, Suci; Pratiwi, Ayu; Aisy, Syifaa’ur Rahmanil (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Anxiety is part of everyday life, where a person experiences an emotional condition or subjective experience involving the psyche, physical, self-perception, and relationships with others. Schizophrenia is a group of psychotic reactions that affect various areas of an individual's functioning, including how to think, communicate, receive, interpret reality, feel and show emotions characterized by chaotic thoughts, delusions, hallucinations, and strange behavior. According to WHO data (2016), there are around 35 million people experiencing depression, 60 million people experiencing bipolar, 21 million experiencing schizophrenia, and 47.5 million experiencing dementia. Progressive Muscle Relaxation (ROP) is a deep muscle relaxation method based on the principle of muscle tension, which is the physiological response of the human body to disturbing thoughts (Cougle et al., 2020). Objective: The purpose of this study was to analyze the effect of Progressive Muscle Relaxation on depression and anxiety in patients with Paranoid Schizophrenia. Method: The method used in this study was community service. Result: The results of the study with a description of community service activities by conducting progressive muscle relaxation group activity therapy, there was a decrease in anxiety levels in Schizophrenia patients with depression and anxiety problems Conclusion: The conclusion from the description of community service activities using the progressive muscle relaxation technique method is that by providing counseling and progressive muscle relaxation therapy, there is a decrease in anxiety levels in schizophrenia patients with depression and anxiety problems.